Ordered Reliability Direct Error Pattern Testing Decoding Algorithm - Hadavian, Reza; Huang, Xiaoting; Truhachev, Dmitri; El-Sankary, Kamal; Ebrahimzad, Hamid; Najafi, Hossein; Ge, Yang; Zokaei, Abolfazl (IEEE transactions on communications, 2025)
We introduce a novel soft-decision decoding algorithm for binary block codes named ordered reliability direct error pattern testing (ORDEPT). The proposed technique tests a list of partial error patterns (PEP)s that are arranged according to their logistic weight and completed on-the-fly based on the instantaneous received sequence and the code's parity-check matrix. Our results, obtained for a variety of popular short high-rate codes, demonstrate that ORDEPT outperforms state-of-the-art decoding algorithms such as ordered reliability bits guessing random additive noise decoding (ORBGRAND) in terms of decoding complexity, and is hardware-favorable in terms of latency and energy consumption. The improvements carry on to the iterative decoding of product codes and convolutional product-like codes, where ORDEPT demonstrates the ability to efficiently find multiple candidate codewords and outperform state-of-the art competitors.